Emergence of carbapenem-resistant Salmonella Typhi harboring blaNDM-5 in India: genomic evidence from a multicenter study - Thirumoorthy, Tharani Priya; Jacob, Jobin John; Teekaraman, Monisha Priya; Mahantesh, S.; Jagannatha, Bhavana; Manasa, Suhani; Nagaraj, Savitha; Savio, Jayanthi; Padaki, Priyadarshini A.; Sudarsana, J.; Nair, Ashalatha; Verma, Sukanya; et al. (Frontiers in Microbiology, 2025)
BackgroundThe rise of antimicrobial resistance (AMR) in Salmonella enterica serovar Typhi poses a serious threat to global enteric fever control. In particular, the emergence of resistance to third-generation cephalosporins and azithromycin critically undermines available treatment options. Sustained genomic surveillance of high-risk S. Typhi lineages and resistance determinants is essential for informing antibiotic policy and optimizing typhoid conjugate vaccine (TCV) introduction in endemic regions. In this study, we report a multicenter outbreak of carbapenem-resistant S. Typhi in India and investigate its genomic epidemiology, resistance mechanisms, and evolutionary origins.MethodsA total of 31 carbapenem-resistant S. Typhi isolates collected from multiple tertiary care hospitals were subjected to phenotypic antimicrobial susceptibility testing and whole-genome sequencing (WGS). Short-read WGS data were used to analyze core-genome SNPs, infer phylogenetic relationships, and investigate AMR determinants. Two representative isolates underwent long-read Oxford Nanopore sequencing for plasmid reconstruction and comparative genomic analysis with Enterobacterales.ResultsAntimicrobial susceptibility testing of isolates revealed resistance to ampicillin, ciprofloxacin, ceftriaxone, and carbapenems while retaining susceptibility to chloramphenicol, cotrimoxazole, and azithromycin. The genomic analysis identified the presence of two plasmids: IncFIB(K) harboring blaCTX-M-15, qnrS1, tetA, and IncX3, carrying the blaNDM-5 gene. Phylogenetic analysis classified the isolates within a novel genotype, 4.3.1.1.1, belonging to genotype 4.3.1.1 (H58 lineage I). Notably, plasmid comparison revealed high similarity to resistance plasmids circulating in co-endemic Escherichia coli and Klebsiella pneumoniae, indicating recent horizontal gene transfer.ConclusionThis is the first documented outbreak of blaNDM-mediated carbapenem-resistant S. Typhi, highlighting a new stage in the evolution of drug-resistant typhoid. The acquisition of high-risk plasmids by S. Typhi and their integration into successful epidemic lineages underscores the urgent need for strengthened genomic surveillance and inter-species AMR tracking. Our findings have direct implications for treatment guidelines, TCV implementation strategies, and efforts to prevent global dissemination of carbapenem-resistant S. Typhi.